DESIGN AND SYNTHESIS OF 1,2,3-TRIAZOLE QUINOLINE ANALOGUES VIA CLICK CHEMISTRY APPROACH AND THEIR ANTIMICROBIAL, ANTIOXIDANT ACTIVITIES - Shirame, Sachin P.; Jadhav, Shravan Y.; B. BHOSALE, RAGHUNATH (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Synthesis of new 1, 2, 3 triazole quinoline derivatives 3a-k using 1, 3-dipolar cycloaddition (click chemistry) reaction of 8-azido-2, 6-dimethoxy-4-methyl-5-(3-trifluoromethyl) phenoxy quinoline with substituted alkynes (3a-k) in the presence of Cu(I) catalyst has been achieved in very high yields. The newly synthesized compounds were characterized by IR, NMR and Mass spectroscopy and evaluated for their antioxidant (H2O2 and OH radical scavenger) and antimicrobial activity. Among the synthesized compounds, the compounds 3h and 3k was found to be an excellent H2O2 radical scavenger as compared to standard ascorbic acid whereas 3f and 3h was found to be good hydroxyl radical scavenger as compared to standard ascorbic acid. Compounds 3a , 3d , 3e, 3f and 3h have shown good antifungal activity as compared to standard drugs griseofluvin and compounds 3b , 3c , 3f and 3h have shown to be moderate antibacterial activity as compared to standard drugs Streptomycin. Keywords: Click chemistry , Quinoline , Antibacterial , Antifungal and Antioxidant activity